Developing university–society partnerships with a focus on climate change impact research using the 'business assist' model (Research for All)
This article explores the experiences generated through a programme of engaged research with university–society partnerships focused on businesses, climate change impacts and environmental technologies. The programme was co-created through research and development collaborations between a university, several large organizations, including the Met Office, Plymouth Marine Laboratory, Regen SW and IBM, and ten small to medium-sized enterprises (SMEs). Through a critically reflective narrative account and two case studies, which represent the perspectives of all involved, this article considers the processes of engagement, their effectiveness, the outcomes delivered and recommendations, as well as the context and influence of European policy – represented by the 'business assist' (BA) model – on creating engaged research. The co-creation of mutually beneficial space emerged as a key success factor, which challenged the short-term focus of the BA model.